Biochemical changes in some banana cultivars infected by Banana bunchy top virus - Rahayuniati, Ruth Feti; Kurniawan, Ruly Eko Kusuma; Nurtiati, Nurtiati (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2024)
Bunchy top is one of the major diseases on bananas that caused economic losses. This study aimed to determine changes in protein content, the concentration of phenolic compounds, the amount of chlorophyll, and sugar content in several Banana bunchy top virus (BBTV)-infected banana cultivars. The research involved the artificial inoculation, extraction, and biochemical analysis of banana seedlings from the cultivars Mas, Cavendish, Kepok, and Raja. Inoculation was performed using the vector Pentalonia sp.. A factorial complete randomized design (CRD) was used as the experimental design. Each experimental unit consisted of 5 repetitions. Protein, phenol, chlorophyll, and sugar content measurements were performed using a UV-Vis spectrophotometer. Test samples were in the form of fresh leaves from BBTV-infected and non-BBTV-infected plants. Regression analysis and tests for significance were performed to determine the biochemical changes that occurred after testing. The results showed that the average levels of phenols, chlorophyll, protein, and total sugars in BBTV-infected plants were significantly altered. The chlorophyll content decreased from 82–87% in Mas, Cavendish, and Raja cultivars. Total plant phenol in all BBTV-infected cultivars increased by 69.2 to 348.3 ppm. Specificity was evident in the change in protein concentration, which increased by 95 ppm and 84.5 ppm in the Mas and Cavendish cultivars, respectively. This contrasts with the Kepok and Raja cultivars, which decreased by 660.5 ppm and 113.6 ppm, respectively. Sugar levels increased from 3133.9 to 3298.6 ppm in all BBTV-infected breeds. According to the data, BBTV infection has been shown to cause physiological and biochemical changes in Mas, Cavendish, Kepok, and Raja.